2015
DOI: 10.1093/molehr/gav054
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of AUF1 and miR-148a destabilizes DNA methyltransferase 1 mRNA under hypoxia in endometriosis

Abstract: This work was supported by the National Science Council of Taiwan (NSC101-2320-B-006-030-MY3). The author declares that there are no conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
0
43
0
3
Order By: Relevance
“…37, 38, 39 In a previous study, DNMT1 could hypermethylate the miR-148a gene promoters in breast cancer tissues, and DNMT1 overexpression resulted in miR-148a hypermethylation. 27 In our study, we found that miR-148a-3p surrounding CpG islands were hypermethylated in bladder cancer and that treatment with 5-aza-CdR induced miR-148a-3p overexpression in bladder cancer.…”
Section: Discussionmentioning
confidence: 93%
“…37, 38, 39 In a previous study, DNMT1 could hypermethylate the miR-148a gene promoters in breast cancer tissues, and DNMT1 overexpression resulted in miR-148a hypermethylation. 27 In our study, we found that miR-148a-3p surrounding CpG islands were hypermethylated in bladder cancer and that treatment with 5-aza-CdR induced miR-148a-3p overexpression in bladder cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Our group has also shown relevance of RNABPs including TTP and HuR as well as localization of TTP in inflammatory conditions using a mouse model of recurrent pregnancy loss 25 . Other RNA binding proteins such as AUF1 have also been shown to have indirect effects by influencing methylation under hypoxic conditions in endometriosis 26 . The adult stem cell marker RNA binding protein, Musashi-1 has been shown to be increased in endometriosis and endometrial carcinomas 27 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that hypoxia promotes the development of endometriosis through various mechanisms. More importantly, a recent study demonstrates that hypoxia causes epigenome reprogramming by stimulating the degradation of DNA methyltransferase 1 mRNA, which results in altering the expression profile of some critical genes involved in the development/progression of endometriosis (Hsiao et al 2015). This suggests that hypoxia may contribute to endometriosis by means of another layer of gene regulation.…”
Section: Endometriosismentioning
confidence: 99%